ANALISIS KELAYAKAN USAHA PENGGILINGAN PADI DI DESA KRANGKONG KECAMATAN KEPOHBARU KABUPATEN BOJONEGORO - Moch Rifqi Shihabuddin Al Ubaidillah; I Made Suparta (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This research aims to analyze the feasibility of a rice milling business in Krangkong Village, Kepohbaru District, Bojonegoro Regency. The analysis used to determine the feasibility of the business is cost analysis, revenue analysis, profit analysis and business feasibility analysis with Rvenue Cost Ratio (R/C Ratio), Benefit Cost Ratio (B/C Ratio) and Return On Infestment (ROI). The results obtained from this research are that the average costs used are IDR 176,475,461/month, the average income obtained is IDR 204,075,000/month and the average profit obtained is IDR 27,599,539/month. Calculating the feasibility analysis of the business, it can be seen that the average value of Revenue Cost Ratio (R/C Ratio) is 1.15, the average value of Benefit Cost Ratio (B/C Ratio) is 0.15 and the average value of Return On Investment (ROI) of 8%. It can be concluded that the rice milling business in Krangkong Village Kepohbaru District Bojonegoro Regency is feasible to run.